IMPLEMENTATION OF MULTICULTURAL ISLAMIC EDUCATION VALUES FOR CHILDREN WITH SPECIAL NEEDS (ABK) AT THE STATE SPECIAL SCHOOL - Sukarno (Universitas Islam Malang, 2024)
Multicultural education in Islam is an integrative effort that combines the values of cultural diversity, tolerance, and inclusion in the education system, with the aim of forming the character of students who are open, respect differences, and are able to live in harmony in a pluralistic society. These values are very relevant in the context of inclusive education in Indonesia, especially for children with special needs (ABK). The Balikpapan City Extraordinary School (SLBN) as an educational institution that serves ABK plays an important role in implementing multicultural Islamic educational values to create a conducive learning environment and support the social, emotional, and academic development of ABK. This study uses a qualitative approach with a case study design to explore how the values of multicultural Islamic education are implemented in SLBN Balikpapan City and identify factors that support and hinder its implementation. Data collection techniques include participatory observation, in-depth interviews, and documentation studies. Participatory observation is used to observe the interaction between teachers and students as well as learning dynamics related to the application of multicultural values. In-depth interviews were conducted with teachers, principals, education staff, and parents of students to gain in-depth insights into implementation strategies and challenges faced. Documentation studies are conducted to analyze various related documents such as curriculum, lesson plans, and school policies. The results of the study show that the application of multicultural Islamic education values in SLBN Balikpapan City is carried out through an inclusive and adaptive approach, with adjustments to learning methods according to the individual needs of students. However, there are various challenges in its implementation, including limited resources, lack of training for teachers, and the need to develop a more inclusive and multicultural curriculum. This research is expected to contribute to the development of better inclusive education practices in Indonesia.